A founder RAB27A variant causes Griscelli syndrome type 2 with phenotypic heterogeneity in Qatari families. Issue 11 (28th August 2020) - Al‐Sulaiman, Reem; Othman, Amna; El‐Akouri, Karen; Fareed, Shehab; AlMulla, Hajer; Sukik, Aseel; Al‐Mureikhi, Mariam; Shahbeck, Noora; Ali, Rehab; Al‐Mesaifri, Fatma; Musa, Sara; Al‐Mulla, Mariam; et al.
Abstract: Griscelli syndrome type 2 (GS2) is a rare autosomal recessive disorder caused by pathogenic variants in the RAB27A gene and characterized by partial albinism, immunodeficiency, and occasional hematological and neurological involvement. We reviewed and analyzed the medical records of 12 individuals with GS2 from six families belonging to a highly consanguineous Qatari tribe and with a recurrent pathogenic variant in the RAB27A gene (NM_004580.4: c.244C > T, p.Arg82Cys). Detailed demographic, clinical, and molecular data were collected. Cutaneous manifestations were the most common presentation (42%), followed by neurological abnormalities (33%) and immunodeficiency (25%). The most severe manifestation was HLH (33%). Among the 12 patients, three patients (25%) underwent HSCT, and four (33%) died. The cause of death in all four patients was deemed HLH, providing evidence for this complication's fatal nature. Interestingly, two affected patients (16%) were asymptomatic. This report highlights the broad spectrum of clinical presentations of GS2 associated with a founder variant in the RAB27A gene (c.244C > T, p.Arg82Cys). Early suspicion of GS2 among Qatari patients with cutaneous manifestations, neurological findings, immunodeficiency, and HLH would shorten the diagnostic odyssey, guide early and appropriate treatment, and prevent fatal outcomes.